2017
DOI: 10.1097/ajp.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Pain Threshold and Anxiety in Adolescent Females With and Without Juvenile Fibromyalgia

Abstract: This study is a first step toward investigating mechanisms of altered pain processing in adolescents with JFM. Adolescents with JFM were found be more sensitive to pressure pain than their healthy peers, which suggests a propensity for sensitization of peripheral and/or central nociceptive information often reported in adult fibromyalgia, and which does not appear to be affected by anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…In a study comparing JFM patients to healthy control, patients with JFM were found more sensitive to pressure pain. They indicated that the results suggest that patients with JFM have a sensitization of peripheral and/or central, like adult fibromyalgia [23]. In the current study, central sensitization values were higher in the group with JFM.…”
Section: Discussionsupporting
confidence: 59%
“…In a study comparing JFM patients to healthy control, patients with JFM were found more sensitive to pressure pain. They indicated that the results suggest that patients with JFM have a sensitization of peripheral and/or central, like adult fibromyalgia [23]. In the current study, central sensitization values were higher in the group with JFM.…”
Section: Discussionsupporting
confidence: 59%
“…PPT is a semi-objective measurement of pain sensitivity, and several studies have shown reduced PPT in chronic pain conditions, especially FM/CWP compared to controls 24,44,49,50 . In agreement with this, we found that PPT was significantly reduced in the FM group compared to CON (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pain tolerance had an inverse pattern in F‐Dys compared to subjects with major depression. Regarding the relationship between anxiety and pain tolerance, the literature has been controversial on this topic, with reports of decreased pain tolerance in post‐traumatic stress disorder or lack of correlation between anxiety and pain tolerance in patients with juvenile fibromyalgia . Yet, we need to recognize that we did not use measures of state anxiety and depression that have been found to modulate pain perception.…”
Section: Discussionmentioning
confidence: 99%